New method for detecting Collectorichum species found in Korea using image analysis - Baek, JeongHo; Kim, Nyunhee; Kim, JaeYoung; Kim, Younguk; Lee, Chaewon; Kim, Song Lim; Ji, Hyeonso; Park, Sang Ryeol; Choi, Inchan; Kim, Kyung-Hwan (Journal of Phytology, 2022)
Colletotrichum acutatum spp. infects various economical crops worldwide and causes massive loss on their yields. Among those, Capsicum spp., which known as chili pepper, is on a critical issue by those pathogens. Due to the lack of their genetic markers in Korea, the unidentifiable various species of C. acutatum obstructs the mechanism studies of these pathogens and the selection of disease resistant breed lines. Therefore, we screened RGB images of the colonization progresses of pathogens to identify the species of Ca40042, K1, NN, AS2, and SW1 by time and temperature. Cultivated pathogens such as Ca40042, K1, and SW1 were detectable on quantified shape and color data of images from specific temperature conditions, while other pathogens were difficult to recognize. Although several limitations exist in identification results of current experiment, but also, we can expect this method can suggest the possibility to replace the genetic marker methods which is now unavailable in Korea.